A construção da língua escrita na pré-escola: um estudo a partir da teoria histórico-social - Rosa, Camila de Sousa (Universidade Federal do Tocantins, 2023)
This work aims to identify the initial course of appropriation of writing by the children. It is understood that preschool is an important stage for the construction of the idea of ​​symbolism and linguistic sign and to understand the appropriation of writing in the preschool period, it is fundamental to identify its origins in the relationships that the child gradually establishes with the of the sign. To understand how learning and development should take place of writing in this school stage, the following specific objectives were defined: to understand how the child begins to understand a symbolic system and signs, such as child begins to perceive writing as a memory resource and what is the role of school. For this, the theoretical-methodological dimension of this study is based on the principles of human development presented by the Historical-Cultural Theory of Vygotsky (2010) which brings with it the importance of mediation and development of higher psychological functions and the prehistory of written language. It is also based on studies by Luria (2010), who points out the paths that make up the prehistory of writing, outlining the origins of this form of language in its genesis, in the preschool period. It also uses reflections by authors such as Mello (2006), Smolka (1988), Geraldi (2011) among others to understand the appropriation process of writing as a historical process how, and in this way, make it possible to rethink teaching of reading and writing. The study pointed out ways for a pedagogical action that creates circumstances that allow the appropriation of writing in its social functionality, providing a qualitative change in the child's relationship with this type of language, because it presents the need to write.